2014
DOI: 10.1371/journal.pone.0105590
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalin Blocks Bladder Cancer Cell Growth In Vitro by Diminishing Cyclin A and cdk2

Abstract: Amygdalin, a natural compound, has been used by many cancer patients as an alternative approach to treat their illness. However, whether or not this substance truly exerts an anti-tumor effect has never been settled. An in vitro study was initiated to investigate the influence of amygdalin (1.25–10 mg/ml) on the growth of a panel of bladder cancer cell lines (UMUC-3, RT112 and TCCSUP). Tumor growth, proliferation, clonal growth and cell cycle progression were investigated. The cell cycle regulating proteins cd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
52
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 32 publications
6
52
0
1
Order By: Relevance
“…Moreover, our results showed that the amygdalin is efficiently induced to the inhibition of cell growth at ∼10 mg/ml concentration as reported in the previous studies (Shragg et al 1982;Chen et al 2013;Makarević et al 2014aMakarević et al , 2014b. However, we interestingly found that the normal somatic cells (MCR-5 fibroblasts) show considerable resistance to the cell growth and senescence at 10 mg/ml concentration of amygdalin.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Moreover, our results showed that the amygdalin is efficiently induced to the inhibition of cell growth at ∼10 mg/ml concentration as reported in the previous studies (Shragg et al 1982;Chen et al 2013;Makarević et al 2014aMakarević et al , 2014b. However, we interestingly found that the normal somatic cells (MCR-5 fibroblasts) show considerable resistance to the cell growth and senescence at 10 mg/ml concentration of amygdalin.…”
Section: Discussionsupporting
confidence: 89%
“…a, b, c and d indicate significant (P < .05) difference among untreated control cell lines, * indicates significant (P < .05) difference between control and 10 mg/ml amygdalintreated cell lines, respectively. modulating β1 or β4 integrin expression (Makarević et al 2014b). These results suggest that amygdalin induces cell cytotoxicity by interfering with the progression of the cell cycle and inducing apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the late 1970s and early 1980s, amygdalin was reported to selectively kill cancer cells at the tumor site without systemic toxicity and to effectively relieve pain in cancer patients (Ellison et al, 1978). Nowadays, there are statistics described that by 1978 more than 70,000 patients with cancers in the United States have been treated with amygdalin (Moss, 2005;Makarević et al, 2014;Qian et al, 2015). However, the use of the drug was discouraged when it was demonstrated that amygdalin is metabolized in the body to release significant amount of cyanide thus leading to cyanide poisoning (Chandler et al, 1984;Bromley et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated the beneficial properties of amygdalin and its ability to effectively induce cell death (Zhou et al, 2012;Chen et al, 2013). Nevertheless, proponents consider amygdalin a natural cancer cure, whereas opponents warn that amygdalin is ineffective and even toxic (Makarević et al, 2014). The endocrine signaling molecules represent source of communication between several organs, as well as specific cell populations.…”
Section: Introductionmentioning
confidence: 99%